CIFOR annual report 2001: forests for the future - Center for International Forestry Research (Center for International Forestry Research, 2002)
Overview of CIFOR’s research and achievements for 2001 including complete financial statements, listings of donors and partners, key projects, staff and publications. The Report also provides the global, regional and national perspectives of CIFOR’s work. Feature stories focus on a range of forest issues, including: carbon, biodiversity, women and forest livelihoods, decentralization in Africa, secondary forests in Asia, forests and fires, forests and health, community forestry, non timber forest products, watersheds in Central America and forest policy in China.